Influence of human saliva on odorant concentrations; Part II: Aldehydes, alcohols, 3-alkyl-2-methoxypyrazines, methoxyphenols, and 3-hydroxy-4,5-dimethyl-2(5H)-furanone. - Büttner, Andrea (Journal of Agricultural and Food Chemistry, 2002)
The influence of human whole saliva on selected alcohols, aldehydes, 3-alkyl-2-methoxypyrazines, and phenols in food-relevant concentrations was investigated. At pH 7.5-8 it was found that the alcohols, methoxyphenols, methoxypyrazines, and 3-hydroxy-4,5-dimethyl-2(5H)-furanone remained unmodified by saliva, whereas aldehydes were reduced to their corresponding alcohols. Generally, the processes were found to be dependent on the salivary activity of the panelists as well as on the concentration of the applied odorants. Reduction of the aldehydes did not occur after thermal treatment of the saliva. These investigations are aimed at finding an explanation for longer lasting aftertaste in humans, as it is induced by some odor-active compounds after the consumption of food materials.<br